2008
DOI: 10.1007/s11255-008-9410-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium supplementation helps to improve carotid intima media thickness in patients on hemodialysis

Abstract: Based on the present data, magnesium may play an important protective role in the progression of atherosclerosis in patients on dialysis. Further studies are needed to assess more accurately the role of magnesium in atherosclerotic regression in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 34 publications
4
122
2
1
Order By: Relevance
“…In accordance with these findings, a recent study in hemodialysis patients showed that magnesium oxide for 6 months was able to decrease carotid IMT with an increase in the placebo group [57]. Indeed, the role of magnesium in attenuating the progression of atherosclerosis has been previously demonstrated in hemodialysis patients [58].…”
Section: Discussionsupporting
confidence: 60%
“…In accordance with these findings, a recent study in hemodialysis patients showed that magnesium oxide for 6 months was able to decrease carotid IMT with an increase in the placebo group [57]. Indeed, the role of magnesium in attenuating the progression of atherosclerosis has been previously demonstrated in hemodialysis patients [58].…”
Section: Discussionsupporting
confidence: 60%
“…At the end of the study, the number of patients with improved carotid IMT was significantly higher in the Mg-containing phosphate binder group than in the Ca-containing binder group (P = 0.04). Turgut et al also showed the beneficial effects of Mg supplementation [76]. However, these findings appeared to be inconclusive because of the relatively small sample size as well as the accuracy and reproducibility of the evaluation methods.…”
Section: Mg-containing Phosphate Bindersmentioning
confidence: 99%
“…Observational studies had shown that low serum Mg may be an independent risk factor for premature death in CKD patients and patients with mildly elevated serum levels could have a better chance of survival over those with lower Mg levels. It has been suggested that Mg supplementation might be useful in reducing the progression of atherosclerosis in chronic dialysis patients (Turgut et al, 2008). …”
Section: +mentioning
confidence: 99%